First‐Principles Prediction of a New Family of Layered Topological Insulators. Issue 11 (13th September 2019) - Li, Ping; Yu, Jiangying; Xu, Jinrong; Zhang, Li; Huang, Kai
Abstract: Dozens of layered V2 IV2 VI6 (V=P, As, Sb, Bi; IV=Si, Ge, Sn, Pb; VI=S, Se, Te) materials are investigated, several of which have been successfully synthesized in experiment. Among them, nine strong topological insulators (TIs), two strong Z2 topological metals (TMs), and nearly twenty trivial insulators are predicted at their equilibrium structures. The TIs are in the (1;111) topological class, with energy gaps ranging from 0.04 to 0.2 eV. The strong Z2 TMs and the trivial insulators belong to the (1;111) and (0;000) topological classes, respectively. Small compressive strains easily turn some of the trivial insulators into strong TIs. This study enriches not only the family of topological materials but also the family of van der Waals layered materials, providing promising candidates for the future spintronic devices. Abstract : Dozens of van der Waals materials V2 IV2 VI6 (V=P, As, Sb, Bi; IV=Si, Ge, Sn, Pb; VI=S, Se, Te) are predicted, including nine topological insulators (TIs), two topological metals, and about twenty conventional insulators. The TIs have in‐plane lattice constants around 7 Å, matching those of Cr2 Ge2 Te6 and CrI3 . This study enriches the families of topological materials and 2D materials.